Insectivores and rodents of the Central Dinaric Karts of Yugoslavia - Kryštufek, Boris (Prirodoslovni muzej Slovenije, 2015)
Twenty-nine species of insectivores and rodents are known to occur in Central Dalmatia, southwestern Bosnia and western Herzegovina: Erinaceus concolor, Sorex minutus, S. araneus, S. alpinus, Neomys fodiens, N. anomalus, Suncus etruscus, Crocidura suaveolens, C. leucodon, Talpa europaea, Clethrionomys glareolus, Dinaromys bogdanovi, Arvicola terrestris, Pitymys subterraneus, P. liechtensteini, Chionomys nivalis, Microtus arvalis, Nannospalax monticola, Apodemus mystacinus, A. flavicollis, A. sylvaticus, Rattus rattus, R. norvegicus, Mus domesticus, M. musculus, Glis glis, Elimys quercinus, Dryomys nitedula, and Muscardinus avellanarius. The distribution in the study area of each of these is discussed and mapped. Available ecological data are compiled and discussed. Zoogeographic relations are discussed. Special attention is paid to small mammal communities from karstic fields. Za osrednjo Dalmacijo, jugozahodno Bosno in zahodno Hercegovino je poznanih devetindvajset vrst žužkojedov in glodalcev: Erinaceus concolor, Sorex minutus, S. araneus, S. alpinus, Neomys fodiens, N. anomalus, Suncus etruscus,Crocidura suaveolens, C. leucodon, Talpa europaea, Clethrionomys glareolus, Dinaromys bogdanovi, Arvicola terrestris, Pitymys subterraneus, P. liechtensteini, Chionomys nivalis, Microtus arvalis, Nannospalax monticola, Apodemus mystacinus, A. flavicollis, A. sylvaticus, Rattus rattus, R. norvegicus, Mus domesticus, M. musculus, Glis glis, Elimys quercinus, Dryomys nitedula in Muscardinus avellanarius. Za vsako vrsto je podana njena razširjenost na preiskovanem obmoèju. Navedeni so tudi razpoložljivi ekološki podatki. V zoogeografski diskusiji posvečamo posebno pozornost malim sesalcem na kraških poljih.